A review on wonder herbs: “Smilax zeylanica” and “Smilax china” - ANJANA MALE, CH K V L S N; SURENDRA, GRANDHI; SANTHI SRI, AKKIRAJU; TEJASREE, A.; MOTHI, SK.SHAHEEN; GULSHAD, SK.; SALMA BAJI, SK.; CHERISHMA, P.; NAZNEEN, SK. (Journal of Neonatal Surgery, 2025)
“Smilax zeylanica” and “Smilax china”, species of the Smilacaceae family, have been Smilacaceae family members have been utilized in classical medicine for their purported therapeutic properties, especially in the treatment of inflammation, pain, and other chronic illnesses. Pharmacological investigations have revealed a wide spectrum of bioactive compounds in these species, including “flavonoids”, “saponins”, alkaloids, and sterols, which contribute to their pharmacological potential. Both species exhibit notable anti-inflammatory, antioxidant, antimicrobial and anticancer activities. “Smilax china” , in particular, has been studied for its potential to modulate metabolic disorders, enhance immune function, and provide cardiovascular benefits. “Smilax zeylanica” has shown promise in managing conditions such as diabetes, arthritis, and skin disorders due to its anti-inflammatory and wound-healing properties. Moreover, these plants' ability to regulate oxidative stress, inhibit pro-inflammatory cytokines, and promote cell apoptosis highlights their role in managing chronic diseases and conditions related to aging. While the medicinal use of Smilax species holds promise, additional investigation is required to clarify their modes of operation, establish safety profiles, and explore their clinical efficacy. This review seeks to synthesize current knowledge on medicinal properties of "Smilax zeylanica" and "Smilax china", and to propose possible directions for further research into their medicinal applications.